Justice in islamic education perspective: Conceptual analysis and implementation in community life - Uswatun Chasanah; Sirojul Baehaqi; Isnaeni Agustina; Muhamad Zulfa; Uswatun Khasanah; Aunillah Ahmad (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Justice is one of the fundamental values in Islamic teachings that has spiritual, social, and legal dimensions. This study aims to analyze the concept of justice from an Islamic perspective and its implementation in social life. The research method used is a literature study with a qualitative descriptive analytical approach, examining primary sources of the Qur'an and Hadith as well as secondary literature in the form of national and international journals. The results of the study indicate that the concept of justice in Islam encompasses three main dimensions: justice towards God (adl ma'a Allah), justice towards fellow human beings (adl ma'a al-nas), and justice towards oneself (adl ma'a al-nafs). The implementation of justice in social life includes economic, legal, social, and political aspects. This study concludes that justice in Islam is comprehensive and holistic, encompassing all aspects of human life with the aim of creating a harmonious and prosperous social order.